Eliciting and analysing expectations of novice distance learners - Cynthia White (Flexible Learning Association of New Zealand, 2012)
This paper reports on an investigation into how 'novice' distance learners conceptualise the process of distance study. In order to elicit reports of expectations and to track shifts in such expectations, data was collected through five phases using questionnaires and interviews. Three cohorts of learners form the sample for different phases of the study: prospective distance learners (N=18), 'novice' distance learners (N=23) and 'experienced' distance learners (N=26) enrolled in the same programmes. The main focus of this paper is on the early phases of the longitudinal study tracking the expectations and shifts in expectations of the novice group, though reference is also made to findings from the prospective and experienced groups. Results are presented concerning the identification of a number of domains of expectations found among prospective distance learners. More detailed findings are given for three of the domains (conceptions of distance learning, success, control) which emerge as central to how novice learners construct their experience in their first two weeks of distance study.